2012
DOI: 10.1186/1747-597x-7-19
|View full text |Cite
|
Sign up to set email alerts
|

Reports of past alcohol and drug use following participation in a motivation enhancing intervention: Implications for clinical assessment and program evaluation

Abstract: BackgroundThere is significant interest in the value of motivational approaches that enhance participant readiness to change, but less is known about clients’ self-reports of problematic behavior when participating in such interventions.MethodsWe examined whether participants in a motivationally-based intervention for DUI offenders changed their reports of substance use at postintervention (when reporting on the same 30 days that they reported on at preintervention). Specifically, Study 1 (N = 8,387) tested wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…We based this decision on previous research indicating that individuals experiencing legal issues based on their substance use and participating in court-ordered intervention report higher levels of previous use when asked following program participation than when queried about the same time period prior to the program [27, 28]. While we cannot be certain these postintervention-collected data were more accurate, we see reason to believe that it might be.…”
Section: Methodsmentioning
confidence: 99%
“…We based this decision on previous research indicating that individuals experiencing legal issues based on their substance use and participating in court-ordered intervention report higher levels of previous use when asked following program participation than when queried about the same time period prior to the program [27, 28]. While we cannot be certain these postintervention-collected data were more accurate, we see reason to believe that it might be.…”
Section: Methodsmentioning
confidence: 99%
“…Except for substance use and related behaviors, all items were asked at pretest and again at posttest. For substance use and related behavior items, we used posttest reports of preprogram behavior, because previous research indicated that individuals with legal issues related to their substance use report higher levels of previous use when asked after program participation than when asked prior to the program (Rosengren et al, ; Stinchfield, ). At baseline, members of this population are usually disgruntled about attending a court‐ordered program and concerned about confidentiality related to their legal entanglements, which are factors hypothesized to decrease the accuracy of self‐report (Del Boca & Darkes, ).…”
Section: Methodsmentioning
confidence: 99%
“…For the 90 days before PFL, we used posttest responses about drinking that occurred during that time period. We based this decision on previous research indicating that court-ordered individuals experiencing legal entanglements based on their substance use and participating in real-world, court-ordered intervention studies report higher levels of previous use when asked following program participation than they had at baseline (Rosengren, Beadnell, Nason, Stafford, & Daugherty, 2012; Stinchfield, 1997). While we cannot be certain this posttest-collected data were more accurate, we reasoned that factors that can decrease the accuracy of self-report—such as unhappiness about attending a court-ordered program, social desirability, and concerns about confidentiality given their legal entanglements (Del Boca & Darkes, 2003)—were likely to be less salient at the posttest time point.…”
Section: Methodsmentioning
confidence: 99%